Website-Based Outpatient Registration Information System at Dokter Bersama Clinic Bojong Gede. - Negara, Mohamad Tirta; Jaenudin, Jejen; Hidayat A, Safaruddin (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
Dokter Bersama Clinic is one of the individual health business entities in Bojong Gede District. However, since the outbreak of the COVID-19 pandemic, the clinic has experienced a decline in income and has temporarily stopped operating. Some time later this pandemic began to decrease and then entered the new normal. The purpose of this study is to reduce the queue for registration crowds of patients who will seek treatment at the clinic and build a website-based outpatient registration system without having to crowd in queues either during the COVID-19 pandemic or after the new normal period. The writing method used is the waterfall method which is classic and easy to use so that it fits with the system design created. The expected results in the Website-Based Outpatient Registration Information System at the Dokter Bersama Clinic Bojong Gede are to help register treatment without having to queue, provide registration information for patients how many queues are running and patients can also choose a treatment schedule according to doctor’s practice hours via online registration and Helping admins and doctors make it easier to manage patient registration with an online system.